The Realization of Expressive Speech Act Used in Smartphone Advertisement Videos on YouTube - Indah Nurhidayah; Pratama, Hendi; Sri Wuli Fitriati (English Education Journal, 2024)
This qualitative descriptive study analyses the use of illocutionary speech acts by pragmatic analysis, especially expressive speech acts, used in 5 selected Samsung advertisements found in YouTube, in which the brands tried to mock or make fun of Apple, its competitor. In its relation to the study of language, advertisements are known employ the functions of language to conduct communication between the sellers or brand producents and the customers, include providing informative and persuasive contents to the customers, in which the brand conveys some message and persuade the consumers to make them buy the products. Just like other kinds of communications, speech acts are employed in advertisements. In comparative advertisements, the brands compare their features to other brands’ to give the audience insight that their products are better than their competitors, and this kind of advertisement is the focus of this study, taking the example of Samsung advertisements with comparing their products to Apple’s. Author used the classification of Searle (1979) in identifying the kind of illocutionary acts in each advertisement. Focusing on the use of expressive illocutionary acts, this study found that not all selected advertisements contain its implementation. From all five selected advertisements, only three advertisements utilize expressive illocutionary speech acts. Expressive illocutionary speech acts found in this study are criticizing, apologizing, boasting, and greeting. This study would be helpful for further research reference and additional insight in learning and discussing expressive speech acts in communication.